1996
DOI: 10.1021/jf960079k
|View full text |Cite
|
Sign up to set email alerts
|

Benzaldehyde Formation from Aspartame in the Presence of Ascorbic Acid and Transition Metal Catalyst

Abstract: Benzaldehyde was produced from aspartame in aqueous acidic solutions containing ascorbic acid and Cu(II) or Fe(III) ion. Benzaldehyde was identified in the system by GC−MS. The yield of benzaldehyde decreases dramatically as the pH of the medium increases above 2.0. EDTA and DTPA completely inhibited benzaldehyde production, while desferrioxamine inhibited only the Fe(III)-catalyzed reaction. Benzaldehyde is not produced under anaerobic conditions unless H2O2 is added to reaction mixtures. H2O2 is produced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The study by Lawrence and Yuan (1996) showed that aspartame, in aqueous acidic solutions in the presence of ascorbic acid and a transition metal catalyst, such as copper (II) or iron (III), under aerobic conditions can produce benzaldehyde via a free radical attack on aspartame. Benzaldehyde production was dependent on ascorbic acid concentration, but the yield of benzaldehyde decreased as the concentration of ascorbic acid exceeded that of aspartame.…”
Section: Stability Of Aspartame In Solutionmentioning
confidence: 99%
“…The study by Lawrence and Yuan (1996) showed that aspartame, in aqueous acidic solutions in the presence of ascorbic acid and a transition metal catalyst, such as copper (II) or iron (III), under aerobic conditions can produce benzaldehyde via a free radical attack on aspartame. Benzaldehyde production was dependent on ascorbic acid concentration, but the yield of benzaldehyde decreased as the concentration of ascorbic acid exceeded that of aspartame.…”
Section: Stability Of Aspartame In Solutionmentioning
confidence: 99%
“…The supernatant collected after centrifugation was diluted accordingly using distilled water and was used as the source of benzaldehyde. The concentration of benzaldehyde expressed as mg benzaldehyde produced g -1 substrate was determined spectrophotometrically at 245 nm (Lawrence and Yuan, 1996) against a standard curve obtained from the commercially available benzaldehyde (Sigma).…”
Section: Extraction and Determination Of Benzaldehyde Concentrationmentioning
confidence: 99%
“…However, the main drawback of the method is the formation of toxic byproducts, such as hydrocyanic acid. Benzaldehyde can also be synthesized chemically via toluene chlorination, however, the process was found to be environmental unfriendly as it requires heavy metals as catalysts with high energy cost and the by-products contain undesirable racemic mixtures (Lawrence and Yuan, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These natural benzyldehyde extracted from fruits contained undesirable toxic by-products such as hydrocyanic acid. Benzyldehyde can also be synthesised chemically, however the process was found to be less environmental friendly as it requires heavy metals as catalyst, high energy cost and the by-products contain undesirable racemic mixtures (Lawrence and Yuan, 1996). Therefore, the production of natural benzyldehyde through fermentation processes was considered.…”
Section: Introductionmentioning
confidence: 99%
“…The supernatant collected after centrifugation was diluted accordingly using distilled water and was used as the source of benzyldehyde. The concentration of benzyldehyde expressed as mg benzyldehyde produced gG 1 PKC was determined spectrophotometrically at 245 rim (Lawrence and Yuan, 1996) against a standard curve obtained from the commercially available benzyldehyde (Sigma). The growth of the fungus was determined by the method described by Swift (1973) based on the spectrophotometric measurement of glucosannine at 530 nm.…”
Section: Introductionmentioning
confidence: 99%